Economic evaluation of biological resources and ecosystem services for the Okhotsk Sea - Olga N. Lukyanova; Igor V. Volvenko; Alla A. Ogorodnikova; Elena N. Anferova (Известия ТИНРО, 2016)
The total cost of commercial stocks of biological resources in the Okhotsk Sea is evaluated as US$ 23.5 · 109/year on the data on total allowable catch for the year 2014, taking into account the world prices for seafood. The potential cost of all known bioresources in the Sea, including pelagic and benthic fish and invertebrates (for a case of their total utilization), is determined as US$ 58.5 · 109/year. The total value of ecosystem services provided by the Okhotsk Sea is estimated as US$ 294.4 · 109/year, believing that their cost per unit area in the Okhotsk Sea is equal to mean value of ecosystem services per unit area in certain areas of the World Ocean with a known cost - this value for non-market ecosystem services exceeds the cost of traditionally used biological resources. Economic evaluation of ecosystem services presented in monetary units can be used as a tool to enhance conservation of natural complexes in the process of industrial projects implementation.